Oral health treatment habits of people with schizophrenia in France: A retrospective cohort study - Denis, Frédéric; Goueslard, Karine; Siu-Paredes, Francesca; Amador, Gilles; Rusch, Emmanuel; Bertaud, Valérie; Quantin, Catherine (PloS one, 2020)
To identify the differences between persons with schizophrenia (PWS) and general population in France in terms of oral health treatment (tooth scaling, dental treatment and tooth extraction) and the factors associated with these differences. This retrospective cohort study included PWS identified from a representative sample of 1/97th of the French population (general sample of beneficiaries). PWS were identified from 2014 data by an algorithm that included: F2 diagnostic codes in the register of long-term diseases in 2014 AND {(at least three deliveries of antipsychotics in 2014) OR (F20 diagnostic codes as a main or associated diagnosis in hospital discharge abstracts in 2012 or 2013 (hospital data for medicine, surgery and obstetrics)}. Follow-up dental care was explored for all people over a period of 3 years (2014 to 2017). In 2014, 580,219 persons older than 15 years were identified from the 96 metropolitan departments in France; 2,213 were PWS (0.4%). Fewer PWS were found along a diagonal line from north-east to south-west France, and the highest numbers were located in urban departments. PWS were more often male (58.6% vs 48.7%, p<0.001). They were less likely to have had tooth scaling but more likely to have undergone a dental extraction. In one third of departments, more than 50% of PWS had at least one tooth scaling over a three-year period; the rate of dental extraction in these departments ranged from 6 to 23%. Then, a quarter of the departments in which 40 to 100% of PWS had had at least one dental extraction (2/8) presented a rate of tooth scaling ranging from 0 to 28% over the study period. Compared with the general population, PWS were less likely to have had tooth scaling and dental treatment but more likely to have undergone dental extraction.